Legal Protection of Child’s Rights Who Conducts of Marriage - Dian Ety Mayasari (Universitas Lampung, 2020)
Every child must be protected and guarded because in addition to the nation's next-generation, also because children have rights in transition. Unfortunately, children cannot enjoy their rights, such as getting an education, playing rights, rights to be creative and to be creative. Law Number 4 of 1979 concerning Child Welfare, Law Number 39 of 1999 concerning Human Rights, Law Number 23 of 2002 concerning Child Protection which was later amended by Law of Law Number 35 of 2014. Implementation of the legality of child protection does not work effectively needs socialization, so that child marriages do not occur and children can enjoy their rights as a child.